Augmented reality in language learning: A state‐of‐the‐art review of 2014–2019 - Parmaxi, Antigoni; Demetriou, Alan A. (My University, 2020)
This systematic review study synthesizes research findings pertaining to the use of augmented reality (AR) in language learning. Published research from 2014 to 2019 has been explored and specific inclusion and exclusion criteria have been applied resulting in 54 relevant publications. Our findings determined: (a) devices and software employed for mastering AR; languages and contexts in which AR had been applied; theoretical perspectives adopted for guiding the use of AR; the number of participants in AR activities and benefits from using AR as an educational tool in the language classroom; (b) alignment of the affordances of Augmented Reality with the KSAVE (Knowledge, Skills, Attitudes, Values, Ethics) 21st-century skills framework; (c) future directions in AR research and practice. The main findings from this review demonstrate the popularity of mobile-based AR for supporting vocabulary (23.9%), reading (12.7%), speaking (9.9%) writing (8.5%) or generic language skills (9.9%). Our findings also uncovered areas that merit future attention in the application of AR in language learning – for instance learning theories were not often considered in the implementation of AR. The study concludes with suggestions for future research especially in the areas of instructional design and user experience.
Keywords: 21st-century skills; Augmented reality; Computer-assisted language learning; KSAVE; Language learning; Pedagogy